The concept of sentence between sentence grammar and text grammar - Mfreg, Hasan Mohammed (Arab Journal for Sciences and Research Publishing, 2019)
Most of researchers in Arabic linguistics tend to believe that they have to choose between sentence’ grammar and text’ grammar. Proponents of old grammarians see that the sentence is the basis of linguistic lessons while specialists in the text’ grammar see that text grammar is the summit of linguistic lessons because it gives tools that assist linguists to analyze texts, as it deals with linguistic compounds used in specific contexts, while the grammar of sentence deals with system sentences that describe language models and do not fall under the framework of completed speech. This research shows the importance of the two types of grammar. First, linguistic lessons start analyzing sentences but eventually the main goal is to analyze texts. So, the relationship between them is an integrative relationship, not a relation based on differences. I consider the text grammar as a cognitive leap since it moves from system sentences to textual sentences which perform communicational functions inside texts. This research tells that by benefiting from both of the two types of grammars, we can find a clear definition for the term of the sentence.
Keywords: Text; Sentence; Grammar; Concept